Red Sea fishes in the Mediterranean Sea: a preliminary investigation of a biological invasion using DNA barcoding. (24th August 2015) - Bariche, Michel; Torres, Martha; Smith, Colin; Sayar, Nancy; Azzurro, Ernesto; Baker, Ryan; Bernardi, Giacomo
Abstract: Aim: More than 90 marine fish species in the Mediterranean have been determined to be alien species of Red Sea origin to date and therefore it is important to prioritize research into cataloguing their distribution and impacts. The aims of this study were to establish a barcode library for alien Mediterranean fishes of probable Red Sea origin and to initiate analyses of their invasion dynamics. Location: Mediterranean Sea. Methods: Specimens of exotic fishes were collected directly from the Mediterranean Sea off the coast of Lebanon or obtained from fish markets in Lebanon. Samples were first identified morphologically and later barcoded using the universal cytochrome c oxidase subunit I ( COI ) mitochondrial marker. Barcodes were compared with GenBank and BOLD database entries and analysed using genetic similarity indexes and neighbour‐joining distance trees. Results: In total, 156 specimens were collected, corresponding to 43 species. The sequence similarity between these sequences and their closest GenBank and BOLD matches ranged between 100% and 83.5%. The 2% genetic distance criterion, often used as a threshold for assigning positive species identification, was met for 31 of 43 (72%) alien species. Sequences from the remaining species (28%) matched species in the databases that were either in the same genus (congeneric) or in the same family (confamilial). In two cases, namely Plotosus lineatus and Sargocentron rubrum, barcoding revealed a possible species complex ( P. lineatus ) and multiple unrecognized species existing in the Mediterranean Sea ( S. rubrum ). Main conclusions: Our study presents a preliminary DNA barcode library, useful for identifying correctly alien fish species of Red Sea origin in the Mediterranean Sea. The results show that most species could be identified, yet the data also uncovered some taxa with unresolved taxonomy and possible cases of unrecognized or cryptic species invasions.